Selecting the money deflator by an encompassing approach: the case of Argentina - Ahumada, Hildegart (2009)
This paper econometrically studies two models of money demand for Argentina. Both characterise the whole sample. Their main difference is the real exchange rate as a determinant whose coefficient estimates implied the exchange rate instead of prices should be used as the money deflator. The model with money deflated by the exchange rate encompasses the model with money deflated by prices. The exchange rate appears to be a proper deflator for hyperinflation experiences and for economies prone to suffer chronic inflation. The choice of the deflator is a key issue for monetary adjustments in response to real exchange rate modifications.